Strategic foresight sebagai Kapabilitas Strategis dalam Transformasi Digital Organisasi Kesehatan: Meta-Sintesis Literatur - Adhein Ayu Mandrakitty; Krisna Dini Septian; Purwadhi Purwadhi; Yani Restiani Widjaja (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2026)
Digital transformation has become a strategic priority for healthcare organizations to improve service quality, operational efficiency, and organizational sustainability. However, previous studies have generally examined strategic foresight, strategic capabilities, and digital transformation as separate constructs, leaving their relationships insufficiently integrated. This study develops a conceptual model of the role of strategic foresight as a strategic capability supporting digital transformation in healthcare organizations through a meta-synthesis approach. Literature was retrieved from the PubMed database using the following inclusion criteria: Scopus-indexed journal articles, published in English, available in full text, and published between 2021 and 2026. Twenty-three articles met the inclusion criteria and were analyzed using thematic synthesis involving coding, descriptive theme development, and analytical theme generation. Five analytical themes emerged: strategic foresight as an anticipatory approach, scenario planning as an implementation mechanism, strategic foresight as an organizational capability, digital transformation as an outcome of strategic capability, and an integrated conceptual model linking environmental change, strategic foresight, strategic capabilities, and digital transformation. The findings indicate that successful digital transformation depends not only on technology adoption but also on an organization's ability to strengthen dynamic capabilities, organizational resilience, and strategic decision-making through strategic foresight. The proposed conceptual model represents the study's main contribution by integrating these elements into a unified framework, providing theoretical insights for strategic management and practical guidance for designing adaptive, proactive, and sustainable digital transformation strategies in healthcare organizations.